Autism and inclusion: teachers' perspectives on the mainstreaming of autistic students - Roberts, Julie-Anne Samantha (My University, 2008)
As a result of White Paper 6 (2001), South Africa has embarked on a radical restructuring of its entire education system, with the aim of removing barriers to learning and including children with disabilities into mainstream schooling (Mittler, 2003). According to this new framework, autistic students should be included into mainstream schools but there is scant research on the feasibility and practical implementation of this. This study took the form of a qualitative analysis of the perceptions of both mainstream and specialised teachers in terms of the mainstreaming of autistic students in South African schools. Results of the study suggest that neither of the sample groups perceive the South African context ready for mainstreaming of autistic students. They felt that students with Aspergers Syndrome, higher-functioning autism, could be included more successfully. However, on the premise that all autistic students were going to be included, a number of changes would need to be made. These included the provison of paraprofessionals, smaller classes and a stronger emphasis on safety. Teachers would also need to receive extensive training on dealing with behavioural problems that autistic students may exhibit. It was further noted that mainstream teachers are in need of practical exposure to autism and training in this area.
Keywords: Autism; Aspergers Syndrome; White Paper 6; Policy of inclusion